2022
DOI: 10.1016/j.cytogfr.2022.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Current utilization of interferon alpha for the treatment of coronavirus disease 2019: A comprehensive review

Abstract: Recent studies have identified an association between perturbed type I interferon (IFN) responses and the severity of coronavirus disease 2019 (COVID-19). IFNα intervention may normalize the dysregulated innate immunity of COVID-19. However, details regarding its utilization and therapeutic evidence have yet to be systematically evaluated. The aim of this comprehensive review was to summarize the current utilization of IFNα for COVID-19 treatment and to explore the evidence on safety and efficacy. A comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 197 publications
0
15
0
Order By: Relevance
“…Indeed, it is known that when IFN‐α has been used to treat thrombocytosis, chronic hepatitis B and C, and certain types of cancer, NAB are associated with loss of clinical effectiveness [ 23 , 24 , 25 , 26 ]. As the risk of developing severe and even potentially fatal COVID‐19 is high in patients with NAB, the optimal use of IFN‐I in COVID‐19 needs to be better defined since its exploration as an emergency treatment in various clinical trials [ 27 ] has excluded patients with demonstrable auto‐Abs to IFN‐α.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is known that when IFN‐α has been used to treat thrombocytosis, chronic hepatitis B and C, and certain types of cancer, NAB are associated with loss of clinical effectiveness [ 23 , 24 , 25 , 26 ]. As the risk of developing severe and even potentially fatal COVID‐19 is high in patients with NAB, the optimal use of IFN‐I in COVID‐19 needs to be better defined since its exploration as an emergency treatment in various clinical trials [ 27 ] has excluded patients with demonstrable auto‐Abs to IFN‐α.…”
Section: Discussionmentioning
confidence: 99%
“…RECOVERY, PRINCIPLE and COLCORONA) [ 219 , 220 ] Interferon alfa Early treatment, either within five days from the onset of symptoms or at hospital admission, confers better clinical outcomes, whereas late intervention may result in prolonged hospitalization. [ 221 ] Interferon beta-1a Interferon beta-1a plus remdesivir was not superior to remdesivir alone in hospitalized patients with COVID-19 and patients treated with Interferon beta-1a who required high-flow oxygen at baseline had worse outcomes. [ 222 ] Interferon lambda Antiviral activity against SARS-CoV-2 virus in vitro .…”
Section: Treatment Of Covid-19 In Patients With Chronic Liver Disease...mentioning
confidence: 99%
“…Because the IFN-I response is down-regulated by coronaviruses, many studies have been conducted to evaluate the effects of interferon treatments (145). In a study involving 11,330 subjects, the World Health Organization has found no benefit of IFN-β1 and recommends against using IFN-I for the treatment of COVID-19 (146).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%